2022-RA-1548-ESGO Trial in progress update on ENGOT-cx8/GOG-3024/innovaTV 205: addition of a new cohort using first-line tisotumab vedotin + pembrolizumab + carboplatin ± bevacizumab in recurrent/metastatic cervical cancer. (20th October 2022) - Vergote, Ignace; Mirza, Mansoor; Sehouli, Jalid; Lorusso, Domenico; Kose, Fatih; Cibula, David; Westermann, Anneke; Collins, Dearbhaile; Banerjee, Susana; Oaknin, Ana; Soumaoro, Ibrahima; Jain, Shweta; et al.
Abstract : Introduction/Background: Despite approval of pembrolizumab + chemotherapy ± bevacizumab as first-line treatment for patients with recurrent/metastatic cervical cancer (r/mCC) whose tumours express PD-L1 (CPS ≥1) and accelerated approval of tisotumab vedotin (TV) monotherapy for patients with r/mCC following disease progression on/after chemotherapy, there remains a need for more effective treatment options. We investigated TV combined with agents with known activity in cervical cancer. A 2-part, multi-cohort phase 1b/2 trial, ENGOT-cx8/GOG-3024/innovaTV 205 (NCT03786081 ), established the recommended phase 2 dose (RP2D) and the feasibility of TV combined with bevacizumab, pembrolizumab, or carboplatin (Monk et al. IGCS 2021). The current report describes the design of a new ongoing dose-expansion cohort in the innovaTV 205 study evaluating the combinations of TV, pembrolizumab, and carboplatin ± bevacizumab. Methodology: The new cohort in the innovaTV 205 study will comprise adult patients with recurrent or stage IVb squamous carcinoma, adenosquamous carcinoma, or adenocarcinoma of the cervix who had no prior systemic therapy and an Eastern Cooperative Oncology Group performance status of 0/1. Patients will be treated with the RP2D of TV (2.0 mg/kg) + carboplatin (AUC 5 mg/mL), pembrolizumab (200 mg), and bevacizumab (15 mg/kg) every 3 weeks or with TV + carboplatin (AUC 5 mg/mL) and pembrolizumab (200 mg). To assess the regimen's initial tolerability, a dose-limiting toxicity evaluation period will consist of completion of 1 treatment cycle of 21 days for 6 patients enrolled to receive the quadruplet combination. The primary end point of this dose-expansion phase is confirmed objective response per RECIST v1.1; secondary end points include duration of response, time to response, progression-free survival, overall survival, and safety. Enrolment is ongoing in the United States and Europe, with additional sites planned globally. © 2022 American Society of Clinical Oncology, Inc. Reused with permission. This abstract was accepted and previously presented at the 2022 ASCO Annual Meeting. All rights reserved.